DNA topology - Bates, Andrew D.; Maxwell, Anthony (Oxford ; New York : Oxford University Press, 2005)
"A key aspect of DNA is its ability to form a variety of structures, this book explains the origins and importance of such structures"--Provided by publisher.
DNA structure -- DNA supercoiling -- DNA on surfaces -- Knots and catenanes -- DNA topoisomerases -- Biological consequences of DNA topology.
Includes bibliographical references and index.
Keywords: DNA -- Structure; DNA -- physiology; DNA -- ultrastructure